Scaling of climate-smart nutrient management advice to smallholder farmers in Tanzania through the Maize-Nutrient-Manager (MNM) decision support tool (2021 UPDATE) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
To increase productivity while limiting GHG emissions, African smallholders need field-specific fertilizer management advice. A new mobile phone application - Maize-Nutrient-Manager - now enables extension workers to not merely provide standard advice messages, but to provide field-specific advice to maize farmers that is tailored to their divergent investment capacities, field conditions and agronomic management.